Hubungan Industrial Meningkatkan Kesejahteraan Buruh - Fatoni, Munir; Widagdo, Gatot; Nugroho, Meysita Arrum (Neolectura, 2024)
The welfare of workers is an aspiration of every laborer. Achieving this welfare is greatly influenced by industrial relations between employers and workers represented by labor unions. A harmonious, dynamic, and fair relationship between both parties is the key to the sustainability of this relationship. This article discusses how open communication, social dialogue, conflict resolution, and active participation of workers can shape a good and sustainable industrial relationship, as well as the government's role in overseeing and regulating this relationship. A qualitative descriptive research method is used to analyze the contribution of all actors in building worker welfare. The results show that good and sustainable industrial relations can increase productivity, create stability within companies, and improve worker welfare.